Implementation of social media learning in elementary school learning - Azhari Ramadhani; Risty Adhia Febianty; Firgi Izdihar Permadi (Himpunan Pengembang Kurikulum Indonesia, 2024)
Social media learning is one form of social media that increases student involvement, collaboration, and learning motivation. This research examines the implementation of social media in elementary school learning, the factors influencing its success, and the obstacles faced. The research method used is a literature study. The literature study method in this research is an initial step in planning research by utilizing the library for data in the field without going directly. Analysis of literature review data was carried out using content analysis. The results of the research show that the implementation of social media learning in elementary school learning indicates that social media learning has a positive influence on elementary school learning, such as 1) expanding access and learning resources for students and teachers; 2) improving critical, creative and collaborative thinking skills students; 3) enrich students' experiences and knowledge about social issues; 4) build exemplary communication and relationships between students, teachers, and parents. Implementing social media learning also positively impacts student learning processes and outcomes, such as increasing student participation, interest, creativity, understanding, and learning achievement. Therefore, social media learning can be used as an effective and innovative alternative learning media in elementary schools. Abstrak Social media learning adalah salah satu bentuk pemanfaatan media sosial sebagai pembelajaran yang dapat meningkatkan keterlibatan, kolaboratif, dan motivasi belajar peserta didik. Penelitian ini bertujuan untuk mengkaji implementasi social media learning dalam pembelajaran sekolah dasar, serta faktor-faktor yang mempengaruhi keberhasilan dan kendala yang dihadapi dalam penerapannya. Metode penelitian yang digunakan dalam adalah studi literatur. Penggunaan metode studi literatur dalam penelitian ini adalah sebagai langkah awal dalam perencanaan pada penelitian dengan memanfaatkan perpustakaan untuk data di lapangan tanpa perlu terjun langsung. Analisis data kajian pustaka dilakukan dengan menggunakan analisis isi. Hasil penelitian menunjukkan bahwa implementasi social media learning dalam pembelajaran sekolah dasar menunjukkan bahwa social media learning memiliki pengaruh positif dalam pembelajaran sekolah dasar, seperti 1) memperluas akses dan sumber belajar bagi peserta didikdan guru;2) meningkatkan keterampilan berpikir kritis, kreatif dan kolaboratif peserta didik; 3) memperkaya pengalaman dan pengetahuan peserta didiktentang isu-isu sosial; 4) membangun komunikasi dan hubungan yang baik antar peserta didik, guru, dan orang tua.Implementasi social media learning juga memberikan dampak positif terhadap proses dan hasil belajar peserta didik, seperti meningkatnya partisipasi, minat, kreativitas, pemahaman, dan prestasi belajar peserta didik. Oleh karena itu, social media learning dapat dijadikan sebagai salah satu alternatif media pembelajaran yang efektif dan inovatif di sekolah dasar. Kata Kunci: pembelajaran; sekolah dasar; social media learning